Managing Water Resources to Maximize Sustainable Growth : A World Bank Water Resources Assistance Strategy for Ethiopia - Sadoff, Claudia (World Bank, Washington, DC, 2012)
This note contains a summary, for practitioners, of the World Bank Country Water Resources Assistance Strategy (CWRAS) report: it concerns managing water resources to maximize sustainable growth and focuses on World Bank water resources assistance strategy for Ethiopia (March 2006). Specifically, the note describes the scope and scale of the impacts of hydrological variability on Ethiopia's economic performance, poverty, natural resources, and socioeconomic conditions, and outlines the Bank's strategic approach to assisting water-related sectors in Ethiopia within an overall development strategy for the country.